a+a(-3)=(a+5)-(a+2)

Simple and best practice solution for a+a(-3)=(a+5)-(a+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a+a(-3)=(a+5)-(a+2) equation:


Simplifying
a + a(-3) = (a + 5) + -1(a + 2)

Reorder the terms for easier multiplication:
a + -3a = (a + 5) + -1(a + 2)

Combine like terms: a + -3a = -2a
-2a = (a + 5) + -1(a + 2)

Reorder the terms:
-2a = (5 + a) + -1(a + 2)

Remove parenthesis around (5 + a)
-2a = 5 + a + -1(a + 2)

Reorder the terms:
-2a = 5 + a + -1(2 + a)
-2a = 5 + a + (2 * -1 + a * -1)
-2a = 5 + a + (-2 + -1a)

Reorder the terms:
-2a = 5 + -2 + a + -1a

Combine like terms: 5 + -2 = 3
-2a = 3 + a + -1a

Combine like terms: a + -1a = 0
-2a = 3 + 0
-2a = 3

Solving
-2a = 3

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by '-2'.
a = -1.5

Simplifying
a = -1.5

See similar equations:

| D=1.3*0.9 | | 9x^2+5x=6 | | c=2*3.14*1.2 | | 9y+9x=0 | | (8a-3b-5c)+(-3a+4b-6c)= | | 3x-34=67 | | y^2=9-4x^2 | | 4x^2+y^2=9 | | 134-10x=7x+19 | | (x^3)-(12x^2)+42x-40=0 | | 6-2x=x-3 | | x^3-3x^2+6x-6=14 | | 17x+19.2y=27 | | 3(x+1)=3(x+3) | | 6y-11=4+9y | | 7z-2=19+4z | | 7x+3=x+19 | | 0.25[7.8+2(2.1)]=x | | -2[6(4-3.6)+0.9]=x | | factorx^2-22x+40= | | 700=400+490y | | 1600=160x+400 | | 6x+3=6x+19 | | 5x-(4x)=-5 | | x+24=63 | | 9x^2+10y^2+40y-50=0 | | 2800=x(1+0.04*3) | | 2800=x(0.04*3) | | 3(6x-4)+3(7-3x)-2(4x+2)=-2 | | .3x^2-1.8-.3=0 | | (x-7)(3x+2)= | | 2(x+1)+2(x+1)=5 |

Equations solver categories